Replacement of cereals by tapioca in rations of Fattening pigs - ΠΑΠΑΔΟΠΟΥΛΟΥ Γ.; ΖΗΡΑ Ε.; ΚΑΛΑΪΣΑΚΗΣ Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
Forty-four pigs (average initial weight 22 Kg), hybrids of Large White and Landrace were divided into seven groups and were fed ad libitum with rations consisted of maize, barley, tapioca, soybean meal, fish meal and wheat bran. During the pre-fattening period the rations contained 13.1-13.4 MJ DE/Kg, 16.2 16.5% crude protein and 0, 20 and 40% tapioca. In the final fattening period however, the rations contained 12.8-13.6 MJ DE/Kg, 13-13.6% crude protein and 0, 20, 40 and 60% tapioca. Part of total replacement of cereals by tapioca reduced the linoleic a cid content of the rations which was added to 1%, except for one group where the linoleic acid content of the ration was 0,45%. The results suggest that tapioca given to fattening pigs up to 40% and 60% during the pre and final-fattening period respectively: (1) did not affect significantly the average daily gain of live weight, (2) improved the coefficient of feed conversion for ρ < 0.05 (3) carcass characteristics were not deteriorated (4) during the replacement of cereals by tapioca to the above proportions the addition of linoleic acid to the ration was not necessary and (5) in order to be economic the use of tapioca, under today Greek conditions, its price should be less than 80% of that of cereals.